Narratives of young people on same-sex relationships about their path and implications for mental health - Andréa Noeremberg Guimarães; Gabriel Deolinda da Silva de Marqui; Maria Luiza Bevilaqua Brum; Carine Vendruscolo; João Marcos Werner; Elisangela Argenta Zanatta (Universidade Federal do Rio de Janeiro, 2019)
ABSTRACT Objective: To know the life path of young people in same-sex relationship from the discovery of their sexual orientation and the confrontation of problems arising from it, contextualizing situations that affect their mental health and reflect on the role of nursing in care, within the scope of Primary Health Care. Method: Qualitative research performed in two public institutions of higher education. Nineteen homoaffective young people participated in the interviews, following a script with open questions related to mental health and same-sex relationship. Data interpretation used the content analysis. Current ethical precepts have been respected. Results: The difficulties of youth concerning the discovery and acceptance of homoaffectivity are related to confrontations in the familiar coexistence and with social groups, cultural and religious aspects. Conclusion and implications for practice: This issue provokes reflections in the nursing professionals concerning the mental health care practices, considering the cultural competence in the Primary Care scope.